Challenges of applying EnvPM in developing countries - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Practically all aspects of business today involve environmental considerations.These considerations, in turn, are being integrated into more and more projects as companies in all industries realize it is not just good public relations but good business too.But environment-related projects are fraught with special risks and difficulties.In carrying out these kind of projects (e.g., altering a manufacturing processes to reduce pollutant), the project manager is confronted with many challenges in addition to the customary constraints of time, budget, quality, resources, etc.These include challenges, such as environmental regulation compliance, responding to public scrutiny, addressing societal values, handling business-government interactions and ensuring workers’ health and safety.